Effects of changes in veno-venous extracorporeal membrane oxygenation blood flow on the measurement of intrathoracic blood volume and extravascular lung water index: a prospective interventional study - Conrad, Alice; Loosen, Gregor; Bösing, Christoph; Thiel, Manfred; Lücke, Thomas; Rocco, Patricia R. M.; Pelosi, Paolo; Krebs, Jörg (Journal of clinical monitoring and computing, 2023)
In severe acute respiratory distress syndrome (ARDS), veno-venous extracorporeal membrane oxygenation (V-V ECMO) has been proposed as a therapeutic strategy to possibly reduce mortality. Transpulmonary thermodilution (TPTD) enables monitoring of the extravascular lung water index (EVLWI) and cardiac preload parameters such as intrathoracic blood volume index (ITBVI) in patients with ARDS, but it is not generally recommended during V-V ECMO. We hypothesized that the amount of extracorporeal blood flow (ECBF) influences the calculation of EVLWI and ITBVI due to recirculation of indicator, which affects the measurement of the mean transit time (MTt), the time between injection and passing of half the indicator, as well as downslope time (DSt), the exponential washout of the indicator. EVLWI and ITBVI were measured in 20 patients with severe ARDS managed with V-V ECMO at ECBF rates from 6 to 4 and 2 l/min with TPTD. MTt and DSt significantly decreased when ECBF was reduced, resulting in a decreased EVLWI (26.1 [22.8-33.8] ml/kg at 6 l/min ECBF vs 22.4 [15.3-31.6] ml/kg at 4 l/min ECBF, p < 0.001; and 13.2 [11.8-18.8] ml/kg at 2 l/min ECBF, p < 0.001) and increased ITBVI (840 [753-1062] ml/m2 at 6 l/min ECBF vs 886 [658-979] ml/m2 at 4 l/min ECBF, p < 0.001; and 955 [817-1140] ml/m2 at 2 l/min ECBF, p < 0.001). In patients with severe ARDS managed with V-V ECMO, increasing ECBF alters the thermodilution curve, resulting in unreliable measurements of EVLWI and ITBVI. German Clinical Trials Register (DRKS00021050). Registered 14/08/2018. https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00021050